Short-term adverse effects of testosterone used for priming in prepubertal boys before growth hormone stimulation test - Albrecht, Andrea; Penger, Theresa; Marx, Martin; Hirsch, Karin; Dörr, Helmuth-Günther (Journal of Pediatric Endocrinology & Metabolism, 2018)
BACKGROUND: Despite the fact that priming with sex steroids in prepubertal children before growth hormone (GH) provocative tests is recommended, there is an ongoing controversial discussion about the appropriate age of the children, the drug used for priming, the dose and the period between priming and the GH test. Interestingly, there is no discussion on the safety of this procedure. To date, only little data have been available on the possible side effects of priming with testosterone. METHODS: We analyzed the outcome in 188 short-statured prepubertal boys who had been primed with testosterone enanthate (n=136: 50 mg; n=51: 125 mg, and accidentally one boy with 250 mg) 7 days prior to the GH test. Serum testosterone levels were measured on the day of the GH test in 99 boys. RESULTS: Overall, only five boys developed adverse side effects. Two boys (dose 125 mg) showed severe low-flow priapism and had to undergo decompression of the corpora cavernosa. One boy suffered from self-limiting priapism and testicular pain (dose 50 mg). Two patients reported testicular pain (each dose 50 mg). The single patient with 250 mg testosterone did not show any adverse effects. The total side effect rate was 2.7%. The serum testosterone levels of the boys with side effects were not different from the testosterone levels of the boys without any side effects. CONCLUSIONS: Parents and patients should be informed about the possible side effects of priming with testosterone such as priapism and testicular pain. However, the overall side effect rate is low. We found no correlation between the outcome and the testosterone dose used and/or the level of serum testosterone.
EVALuna2:35502